From critical accounting to an account of critique: the case of cultural emancipators. Issue 2 (2nd April 2020) - Joannidès de Lautour, Vassili; Wickramasinghe, Danture; Berland, Nicolas
ABSTRACT: Drawing on the Boltanski's sociology of critique, this paper examines how critique contributes to debates in accounting research. Our analysis reveals two responses to critique: (1) reality critiques, uncovering how a research programme is diffused and accepted; and (2) truth critiques questioning object justness and legitimacy. Reality critiques occur before truth critiques but after isolated attempts at emancipation from the dominant perspective. Once the reality critique is articulated, emancipation commences. Truth critiques are not changing events but theorize the rise of isolated attempts at doing differently. In fostering and accelerating emancipation, a critique does not need to be explicitly referenced.